Clinical manifestations of acute asthma in children at the Department of Child Health Cipto Mangunkusumo Hospital - Kadek Ayu Lestari; Imam Budiman; Sudigdo Sastroasmoro (Paediatrica Indonesiana, 2003)
Background Acute asthma is an asthma attack or worsening ofasthma manifestation and pulmonary function. Severe asthma at-tack might be prevented by early recognition of the attack and ap-propriate therapy. Clinical manifestations of asthma in children varywidely, so does the assessment of the attack that is often not accu-rately defined by doctors. This leads to delayed and inadequatetreatment of the attack.Objective This study aimed to know the clinical manifestationsof acute asthma in children at the Department of Child Health, Medi-cal School University of Indonesia/Cipto Mangunkusumo Hospi-tal.Methods This was a descriptive, cross sectional study, conductedat the emergency room (ER), the Pediatric Pulmonology Outpa-tient Clinic, and the Pediatric Outpatient Clinic. Subjects were asth-matics who were having attack and aged 2-18 year-old. Data ofage, sex, pulse rate, respiratory rate, duration of attack, expiratory,and inspiratory effort signs were obtained by history and physicalexamination followed by the assessment of attack severity.Results Subjects consisted of 92 children, mostly obtained fromthe ER (40%), with male to female ratio of 1.5:1 and average ageof 5.8 years old. Most of the subjects had mild attack (83%) andduration of attack of less than 24 hours (56%). Most subjects (70%)only had signs of increased expiratory effort, in which all of themhad mild attack. The rest of the subjects showed the combinationof inspiratory and expiratory efforts; 12 patients with mild attack,15 with moderate attack, and 1 with severe attack.Conclusion Patients who only showed expiratory effort usuallyhad mild attack. Patients showing expiratory and inspiratory ef-forts usually had mild or moderate attack. Treatment should betailored to the degree of attack